2020
DOI: 10.1101/2020.12.01.405910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cholesterol metabolism is a potential therapeutic target in Duchenne Muscular Dystrophy

Abstract: Background: Duchenne Muscular Dystrophy (DMD) is a lethal muscle disease detected in approximately 1:5000 male births. DMD is caused by mutations in the DMD gene, encoding a critical protein that link the cytoskeleton and the extracellular matrix in skeletal and cardiac muscles. The primary consequence of the disrupted link between the extracellular matrix and the myofiber actin cytoskeleton is thought to involve sarcolemma destabilization, perturbation of Ca+2 homeostasis, activation of proteases, mitochondri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 118 publications
(125 reference statements)
5
13
0
Order By: Relevance
“…More recently, we have shown that cardiac function in the mdx mouse is also improved by simvastatin, due in part to the prevention of fibrosis [3]. In strong support of our findings, two recent studies have independently validated our results by showing positive effects of simvastatin treatment in mdx mice [4,5]. In one of these studies, significant improvements in muscle function (force and fatigue resistance), as well as reduced inflammation, fibrosis and plasma CK were comparable to those in our original paper [5].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…More recently, we have shown that cardiac function in the mdx mouse is also improved by simvastatin, due in part to the prevention of fibrosis [3]. In strong support of our findings, two recent studies have independently validated our results by showing positive effects of simvastatin treatment in mdx mice [4,5]. In one of these studies, significant improvements in muscle function (force and fatigue resistance), as well as reduced inflammation, fibrosis and plasma CK were comparable to those in our original paper [5].…”
supporting
confidence: 87%
“…In one of these studies, significant improvements in muscle function (force and fatigue resistance), as well as reduced inflammation, fibrosis and plasma CK were comparable to those in our original paper [5]. In the other paper, widespread perturbations in muscle cholesterol metabolism were discovered in DMD and mdx muscles, and these changes were normalized by simvastatin treatment in dystrophic mice along with reduced plasma CK [4]. Together, our findings and those from two independent research groups provide robust evidence that cholesterol metabolism is abnormal in dystrophic muscles and that simvastatin could provide a novel, inexpensive, and widely used treatment for DMD.…”
supporting
confidence: 64%
“…New treatment approaches to ameliorate the dystrophic phenotype include (i) pharmacological interventions using drugs that modulate the immune response and inflammation, abnormal ion homeostasis, impaired excitation-contraction coupling, cellular growth patterns, abnormal metabolic pathways, cholesterol metabolism, oxidative stress and cardio-respiratory complications [8,132,155,209,214];…”
Section: Therapeutic Implications and Future Perspectivesmentioning
confidence: 99%
“…Whitehead et al cite [1] two recent papers that confirm the therapeutic effects of simvastatin treatment in the mdx mouse model [4,5]. However, the first citation does not mention a dose [4], while the second used delivery via oral gavage of 20 mg/kg simvastatin [5], which would amount to a higher dose of simvastatin than the one we or Whitehead et al used.…”
mentioning
confidence: 99%
“…Whitehead et al cite [1] two recent papers that confirm the therapeutic effects of simvastatin treatment in the mdx mouse model [4,5]. However, the first citation does not mention a dose [4], while the second used delivery via oral gavage of 20 mg/kg simvastatin [5], which would amount to a higher dose of simvastatin than the one we or Whitehead et al used. While these studies confirm the therapeutic effect of simvastatin treatment in mdx mice, they do not confirm that this can be achieved at doses that are in the range of what humans use.…”
mentioning
confidence: 99%